Experimental-Computational Approach to Investigate Nanoindentation of Magnesium Potassium Phosphate Hexahydrate (MKP) With X-CT Technique and Finite Element Analysis - Li, Yue; Zhang, Guosheng; Wang, Zigeng (Frontiers in Materials, 2020)
The magnesium phosphate cement (MPC) is a carbon-free cementitious material, widely used in solidification of nuclear waste, heavy metals and repair and reinforcement. The magnesium potassium phosphate hexahydrate (MgKPO4·6H2O, MKP) is the main hydration product of the MPC, seriously affecting the mechanical properties of the MPC. Therefore, this paper presented an experimental-computational approach to investigate the mechanical properties of the MKP through nanoindentation with X-ray Computed Tomography (X-CT) technique and finite element analysis. Firstly, the micro-mechanical properties and structural distribution characteristics of the MKP were tested based on the nanoindentation and the X-CT technique. Then, the 3D structure grid model of the MKP was obtained based on X-CT data, imported into the ABAQUS software for the finite element simulation. Besides, considering the effect of porosity and pore distribution on the damage, the modified MKP constitutive relation was proposed and input into the X-CT nanoindentation model and the RAP nanoindentation model respectively. It was found that those two models both can effectively describe the mechanical and deformation characteristics of the MKP, which verified the correctness of the modified constitutive relationship of MKP. Finally, the influence of pore distribution on the nanoindentation results was predicted based on the RAP nanoindentation model.